Mathematics in industrial problems - Friedman, Avner (IMA volumes in mathematics and its applications, 1988)
This is the tenth volume in Avner Friedman's collection of Mathematics in Industrial Problems. These books aim to foster interaction between industry and mathematics at the "grass roots" level of specific problems. The problems presented in this book arise from models developed by industrial scientists engaged in research and development of new or improved products.